Case of Mycotic Pseudoaneurysm of the Common Carotid Artery due to Salmonella typhi Bacteremia. Issue 1 (June 2020) - Nair, Sruti P.; Reghukumar, Aravind; Gurudas, Athul; Sasidharan, Kiran Kumar V.; Sivadasan, Sreekumar
Aneurysm of the extracranial carotid artery is a rare disease, mycotic pseudoaneurysms being even less common. They are a life-threatening complication of systemic infection and atherosclerosis. Immunocompromised people, including patients with HIV, uncontrolled diabetes melltus, those on immunosuppressants like high-dose steroids, and chemotherapy, are at a higher risk for development of mycotic pseudoaneurysms. Due to the high risk of potential complications like rupture and thromboembolic events, mycotic aneurysms always require surgical management. Early detection followed by restoration of blood flow is critical to minimize a fatal outcome. Here we report the case of a 52-year-old man with a past history of hypertension and dyslipidemia who presented with a pulsatile painful neck swelling. On evaluation, the patient was diagnosed to have Salmonella typhi bacteremia, HIV infection, and a mycotic aneurysm of the left common carotid artery.